THE HISTORICAL AND CULTURAL CONNECTIONS BETWEEN THE HUNGARIAN PEOPLE AND TURKIC NATIONS (SCIENCE TIME JOURNAL, 2026)
This article explores the deep historical, linguistic, and genetic connections between the Hungarian (Magyar) people and various Turkic nations. It highlights their interactions from the 6th to 9th centuries with Turkic confederations such as the Khazars, Bulgars, and Pechenegs, focusing on cultural exchange, shared nomadic traditions, and mutual influence in language and governance. The study also examines Turkic linguistic traces in Hungarian and recent genetic evidence confirming ancient Central Asian ancestry. The article concludes that the Hungarians’ identity was shaped by centuries of cultural fusion, making them a bridge between East and West.